METHODS FOR RECYCLING POLYVINYL CHLORIDE WASTE - Rayimov Zukhriddin Khayriddin ugli; Khaitov Sadullo Toyir ugli; Khudoyberdiyev Asadbek Ilkhom ugli (Journal Park Publishing, 2025)
This article highlights the environmental impact of polyvinyl chloride waste, the necessity of its recycling, and the practical methods used for its processing. Due to the widespread application of polyvinyl chloride in industrial and domestic sectors, a large amount of waste is generated. The article analyzes thermal, mechanical, and chemical methods for recycling this waste. The technological process, advantages, and disadvantages of each method are examined. Additionally, the most suitable approaches are identified from the standpoint of environmental safety and economic efficiency. The results of the study aim to improve the efficiency of polyvinyl chloride waste recycling and expand the possibilities of using it as a secondary raw material.
Keywords: Polyvinyl chloride (PVC), dioxins, furans, bioaccumulation, ecosystem, polypropylene (PP), polyethylene (PE), pyrolysis, pyrogas, alkaline hydrolysis.